Classic Eosinophilic Pustular Folliculitis in an Immunocompetent Patient with Syphilis: Are They Related? - Li Y; Nie R; Cao X; Wan C (Dove Medical Press, 2023)
Yuchen Li,* Ruxiao Nie,* Xianwei Cao, Chuan Wan Department of Dermatology, The First Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuan Wan, Department of Dermatology, The First Affiliated Hospital of Nanchang University, Yong Wai Zheng Street 17#, Nanchang, 330006, People’s Republic of China, Tel +86-18070052970, Email chuanwan@ncu.edu.cnAbstract: Eosinophilic pustular folliculitis (EPF) is a rare, chronic, non-infectious inflammatory skin disease. Although the pathogenesis of EPF is unknown, eosinophilic pustular folliculitis may be associated with human immunodeficiency virus (HIV) infection, malignancies or syphilis. Here, we report the first case of EPF associated with syphilis, indicating that syphilis and EPF are correlated with T-helper type 2 immune responses. A 48-year-old man gradually developed erythema and pustules on the face, neck. Physical examination revealed multiple infiltrative red patches and plaques on the face, neck with tiny pustules. Skin biopsy results revealed that the dermal follicular sebaceous gland unit was infiltrated by a large number of neutrophils and eosinophils, forming eosinophilic microabscesses. Therefore, the patient was diagnosed with EPF associated with syphilis and received drug treatment. After the treatment, the pustules markedly decreased, leaving behind pigmentation. Furthermore, the patient is still being followed up.Keywords: eosinophilic pustular folliculitis, secondary syphilis, pathogenesis, T-lymphocyte immune response